UJI EFEKTIVITAS EKSTRAK BIJI KETUMBAR (Coriandrumsativum L.) TERHADAP GAMBARAN HISTOPATOLOGI GINJAL TIKUS MODEL HIPERKOLESTEROLEMIADIABETES - Syarifah Nazira, (2020)
Persistent hyperglicemia can trigger the production of oxidative stress. Oxidative stress can cause glomerular hypertrophy. Coriander seed extract has the potential to overcome oxidative stress. This study aims to determine the effect of coriander seed extract to kidney istopathological examination in hypercholestrolemia diabetic rats. Sample consist of 30 males wistar rats were divided into five treatments i.e: (K1) standard feed and aquades, (K2) high-fat feed, alloxan, and glibenclamid 0,045 mg/day, (K3) high-fat feed, alloxan, and coriander seed extract 300 mg/kgBW/day, (K4) high-fat feed, alloxan, and coriander seed extract 500mg/kgBW/day, (K5) high-fat feed, alloxan, and coriander seed extract 700mg/kgBW/day. Coriander seed extract was given for 28 days. The result of Wilcoxon test showed that coriander seed extract can reduce blood cholesterol level in diabetic hypercholesterolemia, meanwhile the result of paired T-test showed that it can reduce blood sugar level. Measurement of kidney's histopathological structure as glomerular area was analyzed by Kruskal Wallis test (p=0,001) and continued with Mann-Whitney test. Group K4 can reduce glomerular area significantly compared with group K3 and K5. In conclussion, coriander seed extract can reduce blood cholesterol, blood sugar level and effectively reduce glomerular hypertrophy at dose of 500mg/kgBW/day.